2018
DOI: 10.1590/1678-98652018000100004
|View full text |Cite
|
Sign up to set email alerts
|

Meal habits and anthropometric indicators in adolescents from public and private schools of the metropolitan region of Rio de Janeiro

Abstract: Objective To describe meal consumption habits and assess their associations with anthropometric indicators. Methods A cross-sectional study was performed on 1,749 elementary and high school students from public and private schools in the city of Rio de Janeiro, Brazil (mean age=15.3 years), who were selected for the baseline of the Longitudinal Study for Nutritional Assessment of Adolescents. Meal habits and meals consumed in the company of parents were assessed using a self-administered questionnaire. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
(69 reference statements)
0
19
0
1
Order By: Relevance
“…Detailed characteristics of each full-text study can be found in Table 2. 25,33,43,54,[56][57][58][59][60][62][63][64][65][66][67][68][69][70][71][72][74][75][76][77][78][79][80][82][83][84][85][86][87][88][89][90][91][93][94][95][96][97] All the studies fitted into 7 exposures developed from the 3 aspects of later eating rhythm. Five of the studies examined 2 exposures each.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed characteristics of each full-text study can be found in Table 2. 25,33,43,54,[56][57][58][59][60][62][63][64][65][66][67][68][69][70][71][72][74][75][76][77][78][79][80][82][83][84][85][86][87][88][89][90][91][93][94][95][96][97] All the studies fitted into 7 exposures developed from the 3 aspects of later eating rhythm. Five of the studies examined 2 exposures each.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Table 3 25,33,55,[57][58][59][60][61][63][64][65][66][67][68][69][70][71][72][73][74][76][77][78][79][80][81][82][84][85][86][87][88][89][90][91][92][93][95][96][97][98][99] outlines the quality assessment of the full-text studies included in the review. Seven studies [66][67][68]77,80,85,91 were described as high quality, losing no more than 2 stars across the 3 domains: sample selection, comparability, and outcome.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…26 Adolescents with higher economic level enjoy goods and present behaviors that may be associated with abdominal obesity, such as technologies that keep them in sedentary activities, 6 non-active commuting means, 27 and poor nutritional-quality foods. 28 There was no association between elevated WHtR and sexual maturation. However, the association of the outcome with age, in girls, may be related to changes in the levels of sexual and growth hormones that occur in the puberty phase, reflecting changes in the body weight and fat distribution.…”
Section: Discussionmentioning
confidence: 88%
“… 26 Adolescents with higher economic level enjoy goods and present behaviors that may be associated with abdominal obesity, such as technologies that keep them in sedentary activities, 6 non-active commuting means, 27 and poor nutritional-quality foods. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Estes autores observaram que meninos com padrão de refeições insatisfatório (omitir regularmente pelo menos uma das três principais refeições) apresentaram maiores médias de IMC e de perímetro da cintura, do que aqueles com padrão satisfatório de refeições. O mesmo foi observado por Cnop et al 33 , em estudantes de escolas públicas e parti-culares, nos quais hábitos irregulares de refeição foram associados com sobrepeso. Neste contexto, observamos que a omissão das principais refeições (desjejum, almoço e jantar), e não apenas do desjejum, pode estar relacionada ao sobrepeso e obesidade.…”
Section: Discussionunclassified